2003
DOI: 10.1167/iovs.02-0946
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular Pressure Measurements Using Dynamic Contour Tonometry after Laser In Situ Keratomileusis

Abstract: Significant decreases in IOP were recorded by GAT after LASIK for myopia. Measurements by DCT, however, did not reveal any significant changes in IOP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
137
3
6

Year Published

2005
2005
2009
2009

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 194 publications
(153 citation statements)
references
References 35 publications
6
137
3
6
Order By: Relevance
“…Several studies showed a significantly lower correlation of CCT with DCT than with GAT. 16,[28][29][30][31] Correspondingly, the present study indicated that DCT readings were statistically independent of CCT, CC, AL, or age. On the contrary, IOP values obtained by GAT depended on CCT but were not significantly influenced by other ocular structural factors and age.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Several studies showed a significantly lower correlation of CCT with DCT than with GAT. 16,[28][29][30][31] Correspondingly, the present study indicated that DCT readings were statistically independent of CCT, CC, AL, or age. On the contrary, IOP values obtained by GAT depended on CCT but were not significantly influenced by other ocular structural factors and age.…”
Section: Discussionsupporting
confidence: 51%
“…Similar results, in spite of different mean values, have been reported by previous investigations. 16,[19][20][21][23][24][25][26][27][28][29][30][31]35,36 The DIOP between DCT and GAT readings was higher in healthy than in glaucomatous eyes, either with open-angle or angleclosure phenotypes (Table 1). The same outcome has been found by analysing IOP measurements obtained by DCT and GAT in different groups of subjects with the same CCT value, except for POAG subjects with thinner corneas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21,24,25 Kaufmann et al 21 compared IOP measurements using GAT and DCT preoperatively and 2 weeks after LASIK in 25 patients and highlighted a significant decrease in GAT-measured IOP postoperatively but no significant change in DCT measured IOP. However, this study was unmasked, limited by the small sample size, and no analysis of agreement between the instruments was attempted.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study comparing dynamic contour tonometry (DCT) and GAT, before and after myopic LASIK correction noted no significant change in DCTmeasured IOP while the GAT-measured IOP decreased significantly. 21 The purpose of the current study was to compare masked IOP measurements obtained by PDCT and GAT and to correlate them with CCT, in a group of patients with normal corneas.…”
Section: Introductionmentioning
confidence: 99%